Role of prebiotics and probiotics in the prevention of the gastrointestinal side effects of metformin among the type 2 diabetic patients - Khan, Sundus; Yousaf, Hira; Rafiq, Hina; Zamir, Zarish; Muhammad Deen, Ayesha; Khan, Tayyab Mumtaz; Nauman, Hina; Nauman, Sheema; Khan, Shahrukh (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetes mellitus (DM) is most common endocrine disorder all over the world. Metformin has been used as a first line drug, however, it has several gastrointestinal side effects. This study aims to determine the frequency of metformin induced gastrointestinal side effects among type 2 diabetic patients and role of prebiotics and probiotics in the prevention of the metformin-induced GI side effects. Methods: This cross-sectional study was performed in a tertiary care hospital, Rawalpindi, among 130 for one year from January 2021 to December 2022. Data was collected by applying a self-structured questionnaire. Descriptive statistics were used for the data analysis. Data analysis was performed via statistical package for the social sciences (SPSS) version 25.0. Results: The means for study variables like age, dose, and duration of therapy were 54.09 years, 1000 mg and 3.6 years respectively. Female patients had more GI side effects than male patients. Similarly, GI side effects frequency was also higher among the patients who were on metformin alone than the patients who were using metformin and combination of prebiotics and probiotics. Patients with higher dose of metformin and shorter duration of metformin therapy had higher frequency of GI symptoms. The most common GI symptom was constipation followed by diarrhea, bloating, abdominal pain, vomiting/nausea, dyspepsia, loss of appetite and flatulence. Conclusions: Metformin induced GI symptoms were common among study population. Use of prebiotics and probiotics combination with metformin, low dose of metformin, and longer duration of metformin use were found protective against the metformin-induced GI side effects.